Gambaran Perkembangan Sosioemosional pada Remaja Perempuan Penyintas Kekerasan Emosional di Panti Asuhan “X” di Ambarawa - S, Stefani Setiaputri; Kristinawati, Wahyuni (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to be able to know and provide an empirical picture related to the description of socioemotional development in adolescent girls who are survivors of emotional violence at Orphanage "X", namely prosocial behavior and empathy development shown by children. This research uses a qualitative approach with a case study research design. In general, the focus of research in qualitative research is holistic (comprehensive, so it cannot be separated), therefore this type of research is determined based on the overall social situation under study. The data sources in this study consist of two sources, namely primary data and secondary data. This research uses triangulation techniques as a data collection technique. In this study, researchers want to analyze the description of socioemotional development, especially prosocial behavior in adolescent girls who are survivors of emotional violence at the "x" orphanage. The conclusion of this study is that it can be seen that the emotional violence experienced by ML and SR has an influence on the socioemotional development of ML and SR. In this case, SR experienced a more severe type of emotional violence than ML.